Literary Materialisations and Interferential Reading
1 online resource (286 pages)
Keywords: This book traces literature's long history of repurposing representational language use for performative, "material" effects. It brings this tradition into dialogue with the recent material turn in literary and cultural theory, which seeks to supplant or at least rethink the foundational influence of the linguistic turn in the field. Drawing on a variety of cutting-edge new-materialist theories, this book programmatically outlines the contours of a methodology of Interferential Reading that is then brought to bear on examples ranging from Shakespeare, Donne, Keats and Tennyson to Northern Irish poets Colette Bryce and Sinéad Morrissey and Scottish poet Kathleen Jamie; from British thing essays to J. G. Ballard, John Berger, Nicola Barker, Richard Powers, Colum McCann, Tim Crouch, Hanya Yanagihara and Korean writer Han Kang, winner of the 2024 Nobel Prize for literature, and from the history of theatrical bodies to the intermedial as well as affective textures in very recent experimental theatre, live theatre broadcasting and media art.